158k views
0 votes
When the quadratic formula is applied to 2x^2 + 3x - 4 = 0, determine the numerator of thesimplified answer.

1 Answer

3 votes

Given:

A quadratic equation is given as


2x^2+3x-4=0

Required:

Apply quadratic formula

Step-by-step explanation:

we have given hat


2x^(2)+3x-4=0

now compare the given equation with


ax^2+bx+c=0

and we get


\begin{gathered} a=2 \\ b=3 \\ c=-4 \end{gathered}

the roots are given as


x=\frac{-b\pm\sqrt[\placeholder{⬚}]{b^2-4ac}}{2a}
\begin{gathered} =(-3\pm√(3^2-4*2*-4))/(2*2) \\ =\frac{-3\pm\sqrt[\placeholder{⬚}]{41}}{4} \end{gathered}

Final answer:


\begin{gathered} x_1=\frac{-3+\sqrt[\placeholder{⬚}]{41}}{4},x_2=\frac{-3-\sqrt[\placeholder{⬚}]{41}}{4} \\ \end{gathered}

User Sbml
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.